Cecil the Lion's Networked Image: The Post-Photographic Media Ecology of Environmental Concern - McManus, Karla (Captures)

(untitled) (Figura, Centre de recherche sur le texte et l'imaginaire, 2016)
Through a study of Cecil the Lion, this article considers the role that digital eco-photography plays in our networked media ecology. As images related to his death were disseminated online, Cecil the Lion became an active artefact of environmentalist mass self-communication. On this occasion, online participatory culture harnessed and renewed the genre of eco-photography for purposes of debate and community building, thus providing new outlets for expressing and promoting moral outrage and censure.